Congenital Hypothyroidism from Birth to One Year of Age Follow up: A Longitudinal - Kawes Omer Zangana (Advanced Medical Journal)
Background and objectives:Congenital hypothyroidism is the commonest neonatal endocrine disorder, and most common treatable causes of mental retardation. The study aimed to find out the important clinical presentations of congenital hypothyroidism at onset of diagnosis and their response to treatment over first year of life.